1995
DOI: 10.1002/pssa.2211510124
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer, infrared, and X-ray studies of the MnZn ferrites

Abstract: Manganese‐zinc ferrite Mn1−xZnxFe2O4 with different values of x is prepared by the usual ceramic technique. X‐ray analysis shows that the samples are cubic spinels (single phase). The lattice parameter, the theoretical density, the bulk density, and the porosity are deduced and their variation with Zn2+ additions is studied. The samples are studied by Mössbauer spectroscopy. The effect of a variation of Zn2+ concentration on the various hyperfine interactions is discussed. The cation distribution of the compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…This is due to the substitution process, that is, replacement of larger ionic radii (Fe 3+ ) by smaller ionic radii (Al 3+ ) and their distribution among the A-and B-sites. These results are in consistent with the reported data [32]. It has been reported that the jump length 'L' (the distance between the magnetic ions) of electrons influences the physical properties of the ferrite system [33].…”
Section: X-ray Diffraction Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…This is due to the substitution process, that is, replacement of larger ionic radii (Fe 3+ ) by smaller ionic radii (Al 3+ ) and their distribution among the A-and B-sites. These results are in consistent with the reported data [32]. It has been reported that the jump length 'L' (the distance between the magnetic ions) of electrons influences the physical properties of the ferrite system [33].…”
Section: X-ray Diffraction Analysissupporting
confidence: 93%
“…It is observed that 'L' of A-and B-sites decreases with increasing aluminum concentration (x) as shown in Figure 3. The decrease in jump length is due to the decrease in the distance between the magnetic ions by the substitution of smaller Al 3+ ions at the B-sites and is similar to those reported earlier [4,32]. Figure 4.…”
Section: X-ray Diffraction Analysissupporting
confidence: 86%
“…3 for samples Ni x Mn 0.8−x Mg 0.2 Fe 2 O 4 (0 ≤ x ≤ 0.40) recorded in the range of 200-800 cm −1 . As usual for spinel ferrites, the band 1 from 633 to 692 cm −1 arises due to the tetrahedral metal-oxygen bond (Fe 3+ -O 2− ) tetra and 2 from 582 to 584 cm −1 is due to the octahedral metal-oxygen (Fe 3+ -O 2− ) octa and these two bands are characteristic for Ni-Mn ferrite as reported elsewhere [11][12][13][14]. Also, it has been reported that [15], Fe 3+ -O 2− distance for A-site (0.189 nm) is smaller than that of B-site (0.199 nm).…”
Section: Resultsmentioning
confidence: 84%
“…The experimental lattice constant is 8.432 Å , which is in agreement with that of bulk Mn 0.3 Zn 0.7 Fe 2 O 4 . 27 However, a small deviation between a th and a exp was observed. This may be because of the presence at the octahedral sites of ferrous ions, Fe(II) (r Fe 2þ = 0.78 Å ), with larger radii than Fe(III) (r Fe 3þ = 0.645 Å ).…”
Section: Resultsmentioning
confidence: 93%